US Withdrawal from Afghanistan: Implications for Pakistan - Sidra Rehman Mughal; Nazir Hussain (Journal of Political Studies, 2017)
The US Exit Strategy 2014 from Afghanistan has now entered one of their final phase, which happens to be the Withdrawal from Afghanistan. The US has already lessened its troops, though there were certain changes after Trump came to power. But still there is a looming confusion which exists regarding the aftermath of the event. That is how this Withdrawal will come to play and what would the Afghanistan’s post-US withdrawal would look like. Moreover, Pakistan will also be affected in more than one ways. The US is going to be leaving quite a vacuum upon which many regional and foreign powers have set their eyes on. India, Iran, China and Russia are all going to be a part of the post-US Afghanistan but this might only produce more instability. Moreover, it will have drastic security, political and strategic implications for Pakistan. The picture which comes to the mind is going to be of an everlasting loop of security complexes and strategic undertones after the withdrawal.